(3Sdhc SHjd GdQTGO dehdGfG GdSdWGf eQGOs
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd edhc GdCfGe Ydi cKjQ ef YHGOg JaVjdG , hLYdge ef MhGOK GdCjGe ai BaGb GdHdGO XdkG XdjdkG s
(3BNQgG (B:s
(3JZeOg ddg HGdQMeI hGdQVhGf , hQhM QhMg ai CYdi ZQa GdLfGf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHI hSde s
(3HgG Jedc dYdi Hf EHQGgje GdHhJjLi GdTGaYis
(3jTJed Ydi JGQjN SdGWjf Bd YKeGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B232 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs